Shelter medicine: a new especialty - Moretto, V. M. S.; Lima, M. O.; Vargas, A. P.; Novais, A. A. (Scientific Electronic Archives, 2016)
Shelter Medicine is a new branch in Veterinary Medicine which aims to improve the health and welfare of animals that do not have a home and live at risk. The specialty was created in the United States of America (USA) with this denomination, and intended the population control of dogs and cats through sterilization, reintegration and socialization of abandoned animals, handling feral cats and control of common diseases in shelters. In this sense, Shelter Medicine proposes a solution to the rampant increase in the non domiciled animals population and, hence, the spread of zoonotic diseases. In addition, to improve the quality of life of those animals, by reducing the euthanasia procedures, damage to property and assault cases